Research and practical issues of enterprise information systems : 12th IFIP WG 8.9 Working Conference, CONFENIS 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-19, 2018, Proceedings /: 12th IFIP WG 8.9 Working Conference, CONFENIS 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-19, 2018, Proceedings. (2018) - Unknown
No abstract available